S95 Clinical outcomes of aspergillus disease phenotypes in adult cystic fibrosis patients. (15th November 2017) - Collier, LJ; Bright-Thomas, RJ; Baxter, C; Richardson, M; Jones, AM
Abstract : Objectives: Aspergillus disease in cystic fibrosis (CF) patients has been proposed to encompass 4 classes: Class 1; No disease, Class 2; Allergic Bronchopulmonary Aspergillosis (ABPA), Class 3; Aspergillus sensitised, Class 4; Aspergillus Bronchitis. 1 The clinical consequence of non-ABPA Aspergillus disease in CF is not fully understood. We evaluated the survival of patients with different classes of Aspergillus disease who were diagnosed as part of Baxter's work between 2008–2011 in order to determine the clinical consequences of the different pheonotypes of disease. Methods: A retrospective case note analysis was undertaken for all 129 patients from the Baxter et al . patient cohort. Survival outcomes were documented for all patients, and baseline demographics including age, gender, FEV1, BMI and co-pathogens were collected. Any patients who received double lung transplantation or who moved away from the unit during this time were identified. The best FEV1 for each year of follow up, FEV1 closest to annual consent date, and BMI were collected for each year of follow in every patient until the current day, or date of death, transplant, or move away. Data was tested for normality and between group comparisons were calculated with one-way anova. Survival was assessed with Kaplan Meier and re-analysed with Cox Regression to adjust for other prognostic factors. Results: There was no statistical significance in survival rates between the 4 classes of Aspergillus disease (P value 0.521). The sole predictor of survival was baseline FEV1 % predicted at time of diagnosis (P value<0.001). Conclusions: There was no statistically significant difference in survival for CF patients with Aspergillus disease over 6–8 years follow up. Further work is being undertaken to continue monitoring and reclassify disease phenotype in this patient cohort. Reference: Baxter et al . J Allergy Clin Immunol2013:132(3).